Militarism, Authoritarianism and Corruption: Post-Coup Honduras and the Decline of Democracy - Pérez, Orlando J.; Wade, Christine J. (Revista Latinoamericana de Opinión Pública, 2023)
This paper uses the Americas Barometer survey series, 2004-2021, consisting of national probability surveys representative of the voting age population to examine the evolution of democratic political culture in Honduras. As our analysis indicates, there has been significant democratic backsliding since 2009. Many of the events we trace in our analysis –the decline of rule of law, rising violence, illegitimate elections, the generalized environment of repression, endemic corruption, and economic decline– are largely the consequences of the 2009 coup and reflect the underlying structural and political conditions that help explain the unprecedented electoral victory of Xiomara Castro in 2021.